ANALISIS PERBANDINGAN METODE TAM DAN UTAUT TERHADAP PENERIMAAN PENGGUNA E-OFFICE DI DPRD BANYUMAS - ito setiawan; Banu Dwi Putranto (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2018)
The Banyumas Regency DPRD is a Regional People's Representative Institution that is located as an organizing element of local government as a representation of the people, Banyumas District DPRD has legislative, budgetary and supervisory functions. To help the process of sending and receiving mail, the E-Office application is used to facilitate transactions. There are obstacles in using the E-Office application, namely the existence of information network interruptions causing delays in the process of correspondence to be disrupted, the number of employees who have not been able to use the application properly, there is no statistical report on the delivery of correspondence. The method used uses the TAM (Technology Acceptance Model) as the method of analysis. The results of this study are all variables from the TAM and UTAUT methods which are tested with the results of H0 being rejected, H1 is accepted meaning that all variables have positive significance